2006
DOI: 10.1111/j.1464-410x.2006.06158.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of uroplakin III expression is associated with a poor prognosis in patients with urothelial carcinoma of the upper urinary tract

Abstract: OBJECTIVE To investigate the association between the expression of uroplakin III (UPIII) and the prognosis of patients with urothelial carcinoma of the upper urinary tract, as uroplakins are urothelium‐specific markers of terminal urothelial differentiation. PATIENTS AND METHODS Clinicopathological and follow‐up data from 71 patients who had undergone radical nephroureterectomy and lymph node dissection or sampling for urothelial carcinoma of the upper urinary tract were reviewed. The expression of UPIII was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Importantly, the loss of UPIII expression was associated with a decrease in cancer-specific survival. Similarly, Ohtsuka et al 17 also found lower UPIII expression in grade III, compared with grades I and II, urothelial tumors, suggesting a correlation between decreased UPIII expression and the level of aggressiveness of the bladder carcinoma. Our study showed that UPIII and UPII protein levels were lower in grade III, compared with grades I and II, bladder tumors ( Table 2).…”
Section: Commentmentioning
confidence: 75%
“…Importantly, the loss of UPIII expression was associated with a decrease in cancer-specific survival. Similarly, Ohtsuka et al 17 also found lower UPIII expression in grade III, compared with grades I and II, urothelial tumors, suggesting a correlation between decreased UPIII expression and the level of aggressiveness of the bladder carcinoma. Our study showed that UPIII and UPII protein levels were lower in grade III, compared with grades I and II, bladder tumors ( Table 2).…”
Section: Commentmentioning
confidence: 75%
“…20 Similar results were found in humans, where loss of UPIII expression was considered a powerful prognostic indicator. 12,16 In a rodent model of chemically induced urinary bladder carcinogenesis, uroplakin expression has been negatively correlated with tumor grade. 15 CK7 labeling was positive and heterogeneous in some cases of urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…8 UPIII shows the highest specificity of this group, but is immunoreactive in only approximately 40-50% of these cases. 9,10 Improved sensitivity can be achieved through a combination of IHC markers, although usefulness in the diagnosis of metastatic lesions and variant morphologies tends to be less robust.…”
Section: Introductionmentioning
confidence: 99%